Periodic Solutions for a Class of 𝑛-th Order Functional Differential Equations - Bing Song; Lijun Pan; Jinde Cao (International Journal of Differential Equations)
We study the existence of periodic solutions for n-th order functional differential equations 𝑥(𝑛)∑(𝑡)=𝑛−1𝑖=0𝑏𝑖[𝑥(𝑖)(𝑡)]𝑘+𝑓(𝑥(𝑡−𝜏(𝑡)))+𝑝(𝑡). Some new results on the existence of periodic solutions of the equations are obtained. Our approach is based on the coincidence degree theory of Mawhin.